Analysis of number needed to treat for droxidopa in patients with symptomatic neurogenic orthostatic hypotension. Issue 1 (December 2016) - François, Clément; Rowse, Gerald; Hewitt, L.; Vo, Pamela; Hauser, Robert
Abstract Background Droxidopa is an orally active prodrug that significantly improved dizziness/lightheadedness measured using the Orthostatic Hypotension Symptom Assessment (OHSA) Item 1 in patients with neurogenic orthostatic hypotension (nOH) caused by primary autonomic failure (Parkinson disease, multiple system atrophy, and pure autonomic failure), dopamine β-hydroxylase deficiency, or nondiabetic autonomic neuropathy. The efficacy and safety of droxidopa were assessed by determining the number needed to treat (NNT) and the number needed to harm (NNH). Methods Data collected in randomized, placebo-controlled clinical studies in adults with a clinical diagnosis of symptomatic nOH were pooled for efficacy and safety analyses. NNT and NNH were calculated as reciprocals of the risk difference (difference in event rates) for droxidopa versus placebo. Results The NNT for droxidopa for improvement in OHSA Item 1 was <10. The NNH for adverse events (AEs) leading to discontinuation in the pooled studies was 81. The likelihood of being helped or harmed (LHH) calculated from pooled analysis of the NNT for ≥2 units of improvement in OHSA Item 1 score and the NNH for discontinuations due to AEs were 7.8, 8.8, 3.1, and 3.5 for weeks 1, 2, 4, and 8 after randomization, respectively. Conclusions Droxidopa is efficacious for treatment of nOH, with an NNT below 10 and an acceptable tolerability profile with NNH ranging from 23 to 302 in the pooled analysis of frequently occurring AEs. Based on the LHH for the pooled analysis at week 1, droxidopa is 7.8 times more likely than placebo to show a clinical benefit than result in discontinuation because of an AE. Trial registrations ClinicalTrials.gov identifiers:NCT00782340, first received October 29, 2008;NCT00633880, first received March 5, 2008; andNCT01176240, first received July 30, 2010.